Rediscovery of Orobothriurus bivittatus (Thorell 1877) stat. n., comb. n. in the Sierra del Tontal, Argentina (Scorpiones, Bothriuridae) - Acosta, Luis E. (Zootaxa, 2005)
The long neglected scorpion species Orobothriurus bivittatus (Thorell) stat. n., comb. n. (Bothriuridae), formerly considered a subspecies of Urophonius brachycentrus (Thorell) and more recently placed under synonymy of the type species of Orobothriurus Maury, O. alticola (Pocock), is revalidated and redescribed on a male captured in the Sierra del Tontal, west Argentina. It proved to be a close relative of O. alticola, from which it can be separated by some details of the hemispermatophore morphology (e.g. relative length of the lamina apex, lobular expansions at the inflexion point of the front crest). This species is probably a high altitude endemic to the Precordillera, a range separated from the Andes (where O. alticola was collected) by a narrow valley. The type locality for O. bivittatus stat. n., comb. n. (and also for Telegonus weijenberghi Thorell) is restricted to the upper belts of the mentioned range, as thoroughly discussed. To ensure nomenclatural stability, it is proposed to set aside the existing holotype and to designate the studied male as neotype.